2018
DOI: 10.1007/978-3-319-98572-5_13
|View full text |Cite
|
Sign up to set email alerts
|

Student Drop-out Modelling Using Virtual Learning Environment Behaviour Data

Abstract: With the rapid advancement of Virtual Learning Environments (VLE) in higher education, the amount of available student data grows. Universities collect the information about students, their demographics, their study results and their behaviour in the online environment. By applying modelling and predictive analysis methods it is possible to predict student outcome or detect bottlenecks in course design. Our work aims at statistical simulation of student behaviour in the VLE in order to identify behavioural pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The Open University Learning Analytics Dataset (OULAD) is used in this study to identify the engagement characteristics of students in a VLE (Kuzilek et al, 2017(Kuzilek et al, , 2018. This anonymized dataset comprises data about courses, students, and their interactions with Open University Virtual Learning Environment for seven selected courses (called modules).…”
Section: Data Descriptionmentioning
confidence: 99%
“…The Open University Learning Analytics Dataset (OULAD) is used in this study to identify the engagement characteristics of students in a VLE (Kuzilek et al, 2017(Kuzilek et al, , 2018. This anonymized dataset comprises data about courses, students, and their interactions with Open University Virtual Learning Environment for seven selected courses (called modules).…”
Section: Data Descriptionmentioning
confidence: 99%
“…In 2018 Kuzilek et al (2018) used Markov chains on the same task as Hlosta et al (2014) with the students' VLE activities generalised to the higher level of abstraction, leading to uncovering a passive withdrawal pattern within the VLE behavioural data. Marques and Belo (2011) applied Markov chains on analysis of behavioural profiles at a Portuguese university.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Considering the factors used to carry out the prediction tasks in OULAD, it can be observed slight differences in the most used factors with respect to the previous general work. Thus, a 39% of studies use the number of accesses to resources (clickstreams) [26,[29][30][31][32][33][34][35], while a 25% of studies combine this information with demographic data from the students [27,28,32,[36][37][38][39]. Focusing solely on assignment information, only one study [40] uses exclusively this factor.…”
Section: Predicting Student Success In Distance Higher Educationmentioning
confidence: 99%
“…Regarding the purpose of the different works, under the main task of predicting student performance, it can be found that the majority of studies pretend to predict whether the student will pass or fail a course [3,27,[30][31][32][37][38][39][40][41][42][43][44][45]. Other approaches focus on the dropout rate [26,29,32,33], while others follow an early prediction study [33,35,36,46]. It is also notable that most studies distinguish among courses or even presentations to make these predictions.…”
Section: Predicting Student Success In Distance Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation